PROFIL PENGGUNA, PREFERENSI INFORMASI DAN FAKTOR YANG BERPERAN PADA PERILAKU MEMBACA LABEL PANGAN PRODUK OLAHAN PETERNAKAN - Wibowo, Candra Pungki (2016)
Label is one of the means of communication to convey product information to be easily understood by the consumers, food labeling in livestock processed products are prepared properly and clearly will make it more feasible for the consumers in choosing the desired product. The purpose of this study is to identify the profile of food labeling in livestock processed products based on age and gender as well as analyzing the types of food label information the types of information of food labels into consumer preferences, deciding factors in the behavior of reading food labels, and the level of consumer knowledge about food labeling. A total of 100 respondents participated in the study. The sampling method using judgmental sampling method with the criteria (1) buy livestock processed products in the last month; (2) male or female with over 18 years of age. Data analysis methods of descriptive statistics and regression.The result of the analysis shows that respondents with a group of 50 year age category, dominantly in female gender, read the food label more compared with other categories. Rating types of food labels that are considered most important are expiration date, the product name, information regarding ingredients, halal labels, nutritional information, how to use and its irregularities, net weight, and the name and the address of the manufacturer. Hypothesis testing can be concluded that risk perception factors affect the behavior of reading the labels of livestock processed product (P<0,05) while factors on health status and availability of shopping time has no influence on reading labels of food labeling in livestock processed products. This study also identified that the majority of respondents as many as 67% have a good understanding of food labels while 32% adequate and only 1% of respondents with less knowledge level.